PENERAPAN MODEL PEMBELAJARAN VISUALIZATION, AUDITORY, KINESTHETIC, TACTILE (MULTI-SENSORY) UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPS SISWA KELAS V SDI NO.178 RAPPOA KAB. JENEPONTO - sri risdawati; R Supardi; Perawati Bte Abustang; Waddi Fatimah (JKPD (Jurnal Kajian Pendidikan Dasar), 2023)
SRI RISDAWATI. 2021. The Application of Visualizatio, Auditory, Kinaesthetic, Tactile (Multi-sensory) Learning Models to Improve Learning Outcomes in Social Studies Subjects for Class V SDI No.178 Rappoa Kab. Jeneponto.Superviset by R. Supardi and Perawati Bte Abustang.This study aims to improve social studies learning outcomes by using Visualization, Auditory, Kinaesthetic, Tactile (Multi-sensory) to improve learning outcomes in social studies subjects for fifth grade students of SDI No.178 Rappoa Kab. Jeneponto. The type of research used is classroom action research and uses a qualitative approach. Data collection technique using observation, tests and documentation. The results of the first and second cycle tests, where in the first cycle there were learning outcomes with an average grade of 64 in the sufficient category, while in the second cycle there were learning outcomes with an average grade of 85 in the very good category. So it can be concluded than in cycle II there has been an increase in student learning outcomes in social studies subjects Class V SDI No.178 Rappoa Kab. Jenepont.Keywords: Learning, Outcomes, Social Studies, Visualization, Auditory, Kinaesthetic, Tactile (Multi-sensory)